Comment on: IgA nephropathy with early kidney disease is associated with increased arterial stiffness and renin-angiotensin system activity. (December 2015) - Mubarak, Muhammed; Nasri, Hamid; Rafieian-Kopaei, Mahmoud
We read with great interest the article by Abdi-Ali et al. entitled "IgA nephropathy with early kidney disease is associated with increased arterial stiffness and renin–angiotensin system activity" in the recent issue of Journal of the Renin–Angiotensin–Aldosterone System . In a study on 10 normotensive IgA nephropathy (IgAN) subjects with early kidney disease and 10 gender- and blood pressure-matched healthy controls, blood pressure and arterial stiffness, expressed as pulse wave velocity and aortic augmentation index, at baseline and in response to 60 min of angiotensin II (AngII) infusion were measured. They found that IgAN patients had an increased aortic augmentation index and a trend towards increased circulating renin–angiotensin system components at baseline, compared with controls.